Influence of intra-skeletal coral lipids on calcium carbonate precipitation12. Issue 46 (8th November 2016) - Reggi, M.; Fermani, S.; Samorì, C.; Gizzi, F.; Prada, F.; Dubinsky, Z.; Goffredo, S.; Falini, G.
Abstract : A study on intra-skeletal lipids from coral shows that they control skeleton porosity. Abstract : Recent research studies have shown that the intra-skeletal organic matrix of corals contains lipids. This communication reports their characterization and their influence on calcium carbonate precipitation. In addition, their potential role in coral's biomineralization is discussed.